If art is a lie that brings us closer to the truth, can Russian literature be read after the Bucha massacre? - Baselica, Giulia (Studia Rossica Posnaniensia, 2025)
The purpose of this article is to propose a reflection based on the question: “Is it possible to read Russian literature after the Bucha massacre?” This question gives rise to a number of reflections, firstly, on the relationship between war and literature, with reference to Theodor Adorno’s famous aphorism; secondly, on the immediate, not infrequent reaction of rejection of any cultural and artistic expression of a Russian nature, with the consequent links to the paradigms of “cancel culture”. On the basis of statements on the subject by Russian and Ukrainian writers, poets and scholars, as well as other interlocutors from Western cultures, an attempt will be made to propose an answer to the first question that is not only dictated by an instinctive impulse, but also by an articulated and, above all, motivated reasoning.